Herpes Virus Reactivation in Astronauts During Spaceflight and Its Application on Earth - Rooney, Bridgette V.; Crucian, Brian E.; Pierson, Duane L.; Laudenslager, Mark L.; Mehta, Satish K. (Frontiers in Microbiology, 2019)
Latent herpes virus reactivation has been demonstrated in astronauts during shuttle (10-16 days) and International Space Station (≥ 180 days) flights. Following reactivation, viruses are shed in the body fluids of astronauts. Typically, shedding of viral DNA is asymptomatic in astronauts regardless of mission duration; however, in some cases, live/infectious virus was recovered by tissue culture that was associated with atopic-dermatitis or skin lesions during and after spaceflight. Hypothalamic-pituitary-adrenal (HPA) and sympathetic-adrenal-medullary (SAM) axes activation during spaceflight occurs as indicated by increased levels of stress hormones including cortisol, dehydroepiandrosterone, epinephrine, and norepinephrine. These changes, along with a decreased cell mediated immunity, contribute to the reactivation of latent herpes viruses in astronauts. Currently, 47/89 (53%) astronauts from shuttle-flights and 14/23 (61%) astronauts from ISS missions shed one or more herpes viruses in saliva/urine samples. Epstein-Barr virus (EBV), varicella-zoster virus (VZV), and herpes-simplex-1 (HSV-1) shed in saliva while cytomegalovirus (CMV) sheds in urine. Larger quantities and increased frequencies for these viruses were found during spaceflight as compared to before or after flight samples and their matched healthy controls. The shedding did not abate during the longer ISS missions, but rather increased in frequency and amplitude. These findings coincided with the immune system dysregulation observed in astronauts from shuttle and ISS missions. VZV shedding increased from 41% in space shuttle to 65% in ISS missions, EBV increased 82% to 96%, and CMV increased 47% to 61%. In addition, VZV/CMV shed ≤ 30 days after ISS in contrast to shuttle where VZV/CMV shed up to 5 and 3 days after flight respectively. Continued shedding of infectious-virus post flight may pose a potential risk for crew who may encounter newborn infants, sero-negative adults or any immunocompromised individuals on Earth. Therefore, developing spaceflight countermeasures to prevent viral reactivation is essential. Our spaceflight-developed technologies for saliva collection/rapid viral detection have been extended to include clinical applications including zoster patients, chicken pox, postherpetic neuralgia (PHN), multiple sclerosis, and various neurological disorders. These protocols are employed in various clinics and hospitals including the CDC and Colombia University in New York, as well as overseas in Switzerland and Israel.